DEVELOPMENT CONCEPT IN EAST BALIKPAPAN WITH MINAPOLITAN APPROACH - Tiara Irawanti; Eko Budi Santoso; Haryo Sulistyarso (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2015)
East Balikpapan district is the largest fish producer in Balikpapan City. The magni-tude of the potential of the fishery is due to waters of East Balikpapan directly oppo-site to the Makassar Strait. But the magnitude of the fisheries’s potency sector in East Balikpapan cannot provide added value to the development of the area yet. When compared with 4 (four) other districts in Balikpapan city, construction on the eastern seaboard of Balikpapan is less developed and less attention impressed. Therefore, the purpose of this study is to develop East Balikpapan by optimizing fisheries resources or referred to minapolitan.This study used four analyses. Growth and share method is used to identify the lead-ing commodities in fisheries sector. Descriptive analysis is used to identify the pro-duction chain of fisheries. Correlation and regression analysis is used to find the factors that influence the development of minapolitan. To arrange the concept of development is using descriptive analysis.The factors that influence the development of Minapolitan in East Balikpapan divid-ed into six factors. Those factors are: fishermen income; linkages between sectors; the production of fisheries; capital; mode of transport; and accessibility. The con-cept of development which can be made starting from upstream subsystem, down-stream subsystem, and supporting subsystem.